SOSIALISASI PENGGUNAAN LITERASI DIGITAL PADA MASYARAKAT DALAM PEKERJAAN PEMELIHARAAN KONSTRUKSI JALAN SERTA BANGUNAN PELENGKAP - Made Novia Indriani; Ida Bagus Wirahaji; Ida Ayu Putu Sri Mahapatni; A.A.A Made Cahaya Wardani (UNHI Press, 2022)
This community service aims to further enrich insight into the condition of road pavement construction and complementary buildings (road drainage and culverts) on environmental roads in Sibanggede Traditional Village, Abiansemal District, Badung Regency. non-governmental activities in maintaining the condition of road pavement construction as access in carrying out various activities, through the activity